microR-4449 Promotes Colorectal Cancer Cell Proliferation via Regulation of SOCS3 and Activation of STAT3 Signaling - Yan, Zhenkun (Cancer Manag Res, 2021)
INTRODUCTION: Dysregulation of microRNAs (miRNAs), which represented a critical level of gene expression modulation, regulated the development of colorectal cancer. However, the functions of numerous miRNAs remain unclear in colorectal cancer. METHODS: The microarray data of GSE115513 were retrieved; subsequently, the differentially expressed miRNAs between 411 colon tumors and 381 normal colon mucosa were analyzed. Real-time PCR (RT-qPCR) and bioinformatic analysis were applied to examine the expression of miR-4449 in collected colorectal tumors and published microarray data. The activity of signal transducer and activator of transcription 3 (STAT3) signaling was detected by Western blotting and RT-qPCR. Dual-Luciferase assay and bioinformatic analysis were used to confirm the interaction between suppressor of cytokine signaling 3 (SOCS3) and miR-4449. Loss of function and rescue assays were performed to study the involvement of miR-4449 and SOCS3 in cell proliferation and apoptosis of colorectal cancer. RESULTS: Herein, we identified miR-4449 as a novel upregulated miRNA in colorectal cancer. Our data suggested that miR-4449 downregulation blocked the proliferation of colorectal cancer cells accompanied with the elevation of cell apoptosis. Decreased expression of miR-4449 led to inactivation of STAT3 pathway as indicated by dephosphorylation of STAT3 and downregulation of STAT3 target genes, including vascular endothelial growth factor (VEGF), c-Myc, baculovirus inhibitor of apoptosis containing 5 (BIRC5). Furthermore, SOCS3, a negative regulator of STAT3 pathway, was found to be a target gene of miR-4449. The data also showed that the inactivation of STAT3 pathway by miR-4449 inhibitor was realized by targeting SOCS3. Moreover, the biological function of miR-4449 downregulation was reversed by SOCS3 knockdown in colorectal cancer cells. CONCLUSION: The current study revealed that miR-4449 promoted cell proliferation of colorectal cancer and was a promising potential therapeutic target for colorectal cancer.